2008
DOI: 10.1016/j.theriogenology.2007.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of re-infection with Neospora caninum in bulls on parasite detection in semen and blood and immunological responses

Abstract: Three bulls with experimentally induced primary infection with Neospora caninum were re-infected intravenously with 10 8 live N. caninum tachyzoites of the NC-1 isolate at 300 days post-infection to investigate the presence of N. caninum in semen and blood, and the associated immune responses. In parallel, three bulls with experimentally induced primary infection with N. caninum and three noninfected bulls were also monitored. Re-infected and infected bulls showed an intermittent presence of N. caninum DNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
1
11
0
1
Order By: Relevance
“…Studies in bulls have shown a similar intermittent pattern of shedding of N. caninum DNA that has continued for more than a year (Serrano-Martinez et al, 2007a;Ferre et al, 2008). By comparison with the closely related protozoan T. gondii, DNA of this organism was also detected in the semen of experimentally infected rams up to 1-month post infection (Teale et al, 1982) which indicates a similar time frame to that seen with N. caninum in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Studies in bulls have shown a similar intermittent pattern of shedding of N. caninum DNA that has continued for more than a year (Serrano-Martinez et al, 2007a;Ferre et al, 2008). By comparison with the closely related protozoan T. gondii, DNA of this organism was also detected in the semen of experimentally infected rams up to 1-month post infection (Teale et al, 1982) which indicates a similar time frame to that seen with N. caninum in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…It is unclear from this current study whether the parasite DNA detected in the semen represents viable tachyzoites as bioassay was not employed to determine if viable tachyzoites were present. In previous studies with experimentally infected cattle, viable tachyzoites could not be detected in bull semen by bioassay (Ferre et al, 2005(Ferre et al, , 2008.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Experiments conducted in the U.S. showed that venereal transmission is possible with a large number of tachyzoites (26). In this study, two out of three bulls sampled were seropositive for antibodies to N. caninum.…”
Section: Discussionmentioning
confidence: 64%